Assessment of Awareness and Preparedness regarding Management of Major Traumatic Haemorrhage in Prehospital Settings amongst EMS Professionals, Pune, India - Parag Rishipathak1 , Navnita Sengupta2 , Anand Hinduja3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: In trauma cases acute major hemorrhage in the first few hours of injury is the leading cause ofdeath in as many as 30% – 40% cases. Major hemorrhage can result in the collapse of the circulatory systemand the patient can present to the emergency room in a state of shock. EMS professionals are expected tohave high degree of awareness as well as should possess the requisite skills and preparedness in the varioustechniques utilized to control life threatening hemorrhage.Aim: To assess the Awareness and Preparedness regarding management of major traumatic hemorrhage inprehospital settings among EMS students.Methodology: The study was conducted amongst 141 Emergency Medical Service professionals. Theoriginal questionnaire consisted of 2 parts, first containing two clinical scenarios testing the awareness leveland the second one containing twenty four items pertaining to the preparedness of EMS professionals inmajor traumatic hemorrhagic situations.Result: The mean score obtained for the parameter awareness was 18.32 out of maximum score of28.Respondents scored well on the parameter pertaining to the management of venous bleeding and amputatedlimb while scored relatively lower on the items pertaining to the management of capillary bleeding.Conclusion: The present study provides encouraging results with regards on the awareness and preparednesslevels of EMS professionals. It also provides insight into future training needs to enhance preparedness incases of infrequent hemorrhagic emergencies.